Effect Of Inclusion Financial And Capital Minimal On Investor Interest In Stock Investment - Opitasari, Juitaselta Seltaopita; Wahyuni, Eka Sri; Yustati, Herlina (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to analyze the effect of financial inclusion and minimum capital on investor interest in stock investment in Bengkulu City. Methodology: This study involved 99 Bengkulu City Investors listed on the Indonesia Stock Exchange in Bengkulu City, using calculation data from a questionnaire via Google Form. Data analysis used descriptive statistical analysis processed using SMART PLS 4.1.0.9. Results: financial inclusion and minimum capital have a positive effect on investor interest in stock investment. Novelty: This study focuses on investors in Bengkulu City, which may not have been widely studied, and combines financial inclusion and minimum capital as influencing factors, a perspective that has not been explored in depth in previous studies. Findings: Indicate that financial inclusion and minimum capital have a significant effect on stock investment interest. Originality: The originality of this study lies in testing the combination of financial inclusion and minimum capital, which has not been explored in depth in previous studies. Conclusion:Â This conclusion summarizes the main findings that indicate that financial inclusion and minimum capital have a significant effect on stock investment interest. Paper Type: Empirical Research paper.